PEMBERDAYAAN MASYARAKAT SUKU TENGGER NGADAS PONCOKUSUMO KABUPATEN MALANG DALAM MENGEMBANGKAN POTENSI TUMBUHAN OBAT DAN HASIL PERTANIAN BERBASIS â€œETNOFARMASIâ€ MENUJU TERCIPTANYA DESA MANDIRI - Listiyana, Anik; Mutiah, Roihatul (Journal of Islamic Medicine, 2017)
Students as well as the next intellectual generation in society is not limited to academic obligations in the campus environment, but also should be useful in a variety of other functions in society. Students are also required to participate in community service through various forms of devotion. In this community service, lecturers with students to jointly work devotion in advancing knowledge and skills Tengger tribe in Ngadas Village District of Poncokusumo in developing the potential of medicinal plants and agricultural products based ethnopharmacy towards the creation of an independent village. Ngadas village is village with abundant natural resources, especially medicinal plants and agricultural products. Medicinal plants rare owned by the village is pronojiwo (Euchresta horsfieldii), pulosari (Alyxia reinwardtii), sintok (Cinnamomum sintoc), purwoceng (Pimpinella pruatjan), krangean (Litsea cububa Pers), flour muscles (Borreria laevis Griseb.), guava wer (Prunus persica Bl.), dringu (Acorus calamus L.). Medicinal plants have the potential to be developed and produced in large quantities in this village. Natural wealth of agricultural products is also very abundant in this village include potato, cassava, sweet potatoes and celery. But not taken into ready to eat foods products. Performed community service on 19 November 2016 in the village hall Ngadas. The activities carried out in the form of workshops begins with exposure of the material on the benefits and applications of potential medicinal plants that become local wisdom in Tengger tribe and then followed by demo making products. The product are rub medicine guava wer,Â  muscle flour, starfruit herbal drinks and bajigur. Participants consisted of PKK Ngadas village. Good response shown by them with great enthusiasm when exposure of the material provided and when making products. In the future, this mentoring program to be developed into entrepreneurial activities of local communities to improve their welfare.